If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 4 + 6m Solving 12 = 4 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 12 + -6m = 4 + 6m + -6m Combine like terms: 6m + -6m = 0 12 + -6m = 4 + 0 12 + -6m = 4 Add '-12' to each side of the equation. 12 + -12 + -6m = 4 + -12 Combine like terms: 12 + -12 = 0 0 + -6m = 4 + -12 -6m = 4 + -12 Combine like terms: 4 + -12 = -8 -6m = -8 Divide each side by '-6'. m = 1.333333333 Simplifying m = 1.333333333
| G(x)=3f(x-2)-4 | | 7T+2=12+5T | | 12=10x+2x | | -2(6n-8)=16-12n | | 4k+7=-4 | | 7K+-8K+-5K= | | 8x-2=-9+nx | | x-.55x=0 | | 1=-15+8x | | 12=1.5 | | 2(3x-5)=9-(2x-5) | | 0.2x-6=x | | 2(5d+3)=4d | | -5.6+12.2=5h | | 4(m-3)=-32 | | 4x+6x+1=0 | | x^2-5=sqrt(3*x) | | -23-2p=19-p | | 12x^2+35x-3=0 | | 7=9(2f+5) | | 3(2x+3)=4-x | | 4w-7=3w+1 | | x^2+18x+30=0 | | 4x-5=4x-9 | | 1/2n+5/6=2/3 | | (6x+2)+20=90 | | -8-7x-6x=-8 | | 18=a(a-7) | | 4x=14x-30 | | 6b+15=4b+19 | | -84=-7(x+5) | | (6x+2)+20=360 |